What determines the importance of a species for ecosystem processes? Insights from tropical ant assemblages - Houadria, Mickal; Menzel, Florian (Oecologia, 2017)
Biodiversity is known to increase ecosystem functioning. However, species vary in their contributions to ecosystem processes. Here, we investigated seven ecosystem functions based on the consumption of different resources in tropical ant communities. We analysed how different species influence site-level resource consumption, and determined how each species influenced performance and stability of these functions. Based on simulated extinctions, we identified 'key species' with significant functional contributions. We then investigated which traits, such as biomass, abundance, and specialisation, characterized them, and compared trait distributions across four sites to analyse differences in functional redundancy. Only few species significantly influenced ecosystem functions. Common generalist species tended to be the most important drivers of many ecosystem functions, though several specialist species also proved to be important in this study. Moreover, species-specific ecological impacts varied across sites. In addition, we found that functional redundancy varied across sites, and was highest in sites where the most common species did not simultaneously have the greatest functional impacts. Furthermore, redundancy was enhanced in sites where species were less specialised and had more even incidence distributions. Our study demonstrates that the ecological importance of a species depends on its functional traits, but also on the community context. It cannot be assessed without investigating its species-specific performance across multiple functions. Hence, to assess functional redundancy in a habitat and the potential for compensation of species loss, researchers need to study species-specific traits that concern functional performance as well as population dynamics and tolerance to environmental conditions.
Keywords: Functional performance; ekosystém; biodiverzita; ekologie; Ecosystem processes; Ecology; zvířata; populační dynamika; Species Specificity; Biodiversity; Resource consumption; druhová specificita; Biomass; Ants; Population Dynamics; Ecosystem; Functional redundancy; biomasa; Formicidae; Animals